Lash Impaction in Meibomian Gland Orifice - Mansour AM (Dove Medical Press, 2020)
Ahmad M Mansour,1,2 Khalil M El Jawhari3 1Department of Ophthalmology, American University of Beirut, Beirut, Lebanon; 2Department of Ophthalmology, Rafic Hariri University Hospital, Beirut, Lebanon; 3Medical University of Lodz, Lodz, PolandCorrespondence: Ahmad M MansourDepartment of Ophthalmology, American University of Beirut, PO Box 113-6044, Beirut, LebanonTel +9613377633Email ammansourmd@gmail.comPurpose: To analyze potential risk factors associated with eyelash impaction into meibomian gland orifice.Methods: Retrospective review of one tertiary clinic over a period of 10 years.Results: In this study, 18 patients were included, with a mean age of 61.6 years at diagnosis. Ten patients were symptomatic in the form of ocular irritation or foreign body sensation. The location of the impaction included 15 nasal half and 3 temporal half of the lid, 6 upper lid and 12 lower lid, 8 right side and 10 left side. Risk factors included dry eyes (10), allergic conjunctivitis (4), severe rubbing of the eye (6), sleeping on the eye (2), and recent phacoemulsification (1).Conclusion: Ocular rubbing from either ocular allergy or dryness is associated with impaction of the lash into the orifice of the meibomian gland duct.Keywords: cilia, eyelash, lash impaction, meibomian gland duct orifice